التنسيق بين الكليَّات والجزئيّات وأثره في الاجتهاد والترجيح الفقهي - محمد هندو (International Institute of Islamic Thought, 2013)
يعرض هذا البحث بالتعريف والتأصيل والتحليل لمنهجية جليلة في التعامل مع الأدلة الشرعية، واستدرار الأحكام على ضوئها، وهي التنسيق بين كليات المدارك وجزئياتها، والبحث مقسم إلى أربعة أقسام: أولها في بيان حقيقة الكليات والجزئيات وحقيقة التنسيق بينهما، وثانيها في تأصيل منهج التنسيق، وبيان مقوماته الأساسية مع التركيز على فكر الإمام الشاطبي باعتباره شيخ المنهج بحق، وثالثها في بيان الخطط الاجتهادية الكفيلة بهذا التنسيق، ورابعها في بيان أثر قضية البحث على الاجتهاد والترجيح الفقهي من خلال تطبيقات معاصرة يتجلى فيها المنهج المنشود بوضوح. This paper presents the definition and analysis of a great methodology of dealing with the Shari'a evidences and extracting the rules in its light. It is the methodology of coordination between general and particular legal evidence. The is divided into four sections; the first one explains the concept of general and particular evidences and the meaning of coordination between them; the second section discusses the establishment of the methodology and explaining its basic components based on the word of Imam Al-Shatibi, the pioneer of this field. The third section explains procedures of this coordination in the line with this approach. Finally the fourth section and discusses the impact of coordination issue on juristic ijtihad and weighting of different evidences, based on contemporary practical applications.